2016
DOI: 10.3389/fnbeh.2016.00048
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Communicative Abilities in Patients with a History of TBI: Behavioral Improvements and Cerebral Changes in Resting-State Activity

Abstract: A targeted training program for the rehabilitation of communicative abilities—Cognitive Pragmatic Treatment (CPT)—has been developed and previously tested on a sample of patients with traumatic brain injury (TBI), whose performance was found to have improved. Since cortical plasticity has been recognized as the main mechanism of functional recovery, we investigated whether and how behavioral improvements following the training program are accompanied by brain modifications. Eight TBI patients took part in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 64 publications
1
17
0
1
Order By: Relevance
“…In a similar vein, Chiaravalloti et al 11 reported that, in parallel with a decreased activation in the supplementary motor and dorsolateral prefrontal area, there was an increased activation of the left posterior cingulate cortex, right anterior cingulate cortex, and posterior insula. A higher activation of similar circuits, described as part of the default mode network, has also been reported by Sacco and colleagues in their article on communication, 19 thus showing that this network may be modified by cognitive rehabilitation, with consequent changes in functional connectivity. Although none of the studies analyzed in this review have specifically focused on the latter aspect, it is now widely established that a defective connectivity may significantly condition the cognitive performance of brain injured subjects 50,[90][91][92] : diffuse axonal damage (DAI), typical of moderate to severe TBI, may cause axons fragmentation and tearing, 93,94 leading to a diminished or interrupted integration of information processing across spatially distinct brain regions.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a similar vein, Chiaravalloti et al 11 reported that, in parallel with a decreased activation in the supplementary motor and dorsolateral prefrontal area, there was an increased activation of the left posterior cingulate cortex, right anterior cingulate cortex, and posterior insula. A higher activation of similar circuits, described as part of the default mode network, has also been reported by Sacco and colleagues in their article on communication, 19 thus showing that this network may be modified by cognitive rehabilitation, with consequent changes in functional connectivity. Although none of the studies analyzed in this review have specifically focused on the latter aspect, it is now widely established that a defective connectivity may significantly condition the cognitive performance of brain injured subjects 50,[90][91][92] : diffuse axonal damage (DAI), typical of moderate to severe TBI, may cause axons fragmentation and tearing, 93,94 leading to a diminished or interrupted integration of information processing across spatially distinct brain regions.…”
Section: Discussionsupporting
confidence: 59%
“…Conversations in TBI individuals are less interesting, less appropriate, more confused, and inefficient than those of non-brain-injured controls. 73 Studies analyzing the efficacy of cognitive treatment for the improvement of communicative abilities in severely brain injured subjects include that carried out by Sacco et al 19 In their work, the authors investigated the behavioral and neural modifications induced by cognitive pragmatic treatment in a group of TBI participants. 74 Interestingly, the neuroimaging measure used in this study did not consist of task-related fMRI, as in the previous studies: a resting state paradigm was used to investigate neural modification occurring after rehabilitation sessions.…”
Section: Communicative and Pragmatic Abilitiesmentioning
confidence: 99%
“…Although our previous studies [18][19][20][21] and those of others 22,23 demonstrated neuroplasticity after cognitive training in TBI, little is known about training-induced changes in the full-scale organization of the brain networks in individuals with TBI. Because the assessments of whole-brain networks in TBI utilizing rsfMRI and graph theory have provided insights into the brain systems disrupted by DAI, 3,5,6,[8][9][10][11][12] it would be informative to identify training-related neuroplasticity in TBI at the whole-brain level.…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, the CPT focuses on components such as awareness, theory of mind, and executive functions, which play a role [ 11 , 33 ] in structuring efficient communication. The training has already been used with TBI individuals [ 34 , 35 ] and in a pilot study with patients with schizophrenia [ 36 ], revealing high rates of effectiveness in improving their communicative performance.…”
Section: Introductionmentioning
confidence: 99%